Identifikasi Bahaya, Analisis Risiko Dan Penanggulangan Risiko Pada Petani Lada Di Kecamatan Air Naningan Kabupaten Tanggamus: Asri Dyah Azhari, Ester Metalia Agusta, Mega, Putri Suci Rulliyani, Elfiera Rose Anna Miyako, Monia Agista, Fitri Yana, Fitria Saftarina - Monia Agista; Asri Dyah Azhari; Fitria Saftarina; Fitri Yana; Ester Metalia Agusta; Mega; Putri Suci Rulliyani; Elfiera Rose Anna Miyako (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2026)
The pepper (Piper nigrum) farming sector plays a strategic role in the Indonesian economy, but carries a high risk to occupational safety and health (OHS). This study aims to identify potential hazards, analyze and assess risk levels, and determine work risk control efforts at each stage of pepper cultivation activities using the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method. This study uses a descriptive design with a mixed methods approach. The study was conducted in March–April 2026 in Air Naningan District, Tanggamus Regency, involving 6 active pepper farmers as respondents who were selected using a purposive sampling technique based on the criteria of farmers who actively cultivate pepper and are willing to be respondents. Data were collected through direct observation, in-depth interviews, and field documentation. Data were collected through observation, interviews, and documentation. The results showed that potential hazards include physical, chemical, biological, ergonomic, environmental, and psychosocial aspects. The risk assessment indicated that most activities were categorized as moderate to high risk, especially in land clearing, pesticide use, and harvesting and post-harvest activities. Low use of personal protective equipment (PPE) and the lack of implementation of OHS principles were the main factors increasing the risk. Risk control efforts need to be carried out through the implementation of a control hierarchy, increasing farmer education, and cross-sector support to improve farmer safety and productivity in a sustainable manner. Keywords: HIRARC,occupational health agriculture, pepper farming, risk management